Análisis de los significados que intervienen en la apropiación del espacio desde los socios del comité de desarrollo comunitario los pinos en los años 2015-2016 - Mantilla Aguilar, Cristian Andrés (2017)
The present work aims to approach the concept of appropriation of space in the reality of a self-defined organization as Comité de Desarrollo "Los Pinos" located in the parish of Cutuglagua, starting from the community environmental psychology and other theoretical aspects that analyze the environment linked to the social relations of a community. It's also important to mention that the appropriation of space is a category of social analysis in conjunction with the manifestations of a group related to its space, therefore has a socio-historical basis of the processes of articulation of human groups and their environments. Also the elements that recover value in this document are the sense of community, attachment to the place, identity; concepts that are intrinsic to the processes of conformation of the communities, where the relations with its surroundings and the interrelations allow to construct places loaded with symbolic sense; therefore the spaces of a community become places where social cohesion is perceived in their daily dynamics and also where recognition with the other has a genesis from the vital historical identification of each individual. It's also important to mention that the appropriation of space beyond being a formal category is a social dimension that is articulated in the daily life of social life, not only from the issue of legality of land, but from the relational links of the subjects with their realities.